Ti/ e)moi kai soi/, gu/nai; (John 2:4) Philological, Contextual, and Exegetical Arguments for the Understanding: “What Does This Matter to Me and to You?” - Ramelli, Ilaria L.E. (Exemplaria Classica, 2008)
Sin resumen